Trigonometry (11th Edition) Clone

Published by Pearson
ISBN 10: 978-0-13-421743-7
ISBN 13: 978-0-13421-743-7

Chapter 6 - Inverse Circular Functions and Trigonometric Equations - Section 6.4 Equations Involving Inverse Trigonometric Functions - 6.4 Exercises - Page 286: 31



Work Step by Step

Given: $2arccos(\frac{y-\pi}{3})=2\pi$ $arccos(\frac{y-\pi}{3})=\pi$ $(\frac{y-\pi}{3})=cos(\pi)$ $(\frac{y-\pi}{3})=-1$ $({y-\pi})=-3$ Hence, $y=\pi-3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.